Moral decision-making attitude and psychological well-being: reflections from various sports branches - Arif Özsarı; Alpaslan Görücü (Physical Education of Students, 2023)
Background Study Aim. This study aimed to investigate the impact of moral decision-making attitudes among athletes in various sports on their psychological well-being.